1999
DOI: 10.1128/jvi.73.3.2568-2568.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Kaposin (Open Reading Frame K12) as a Human Herpesvirus 8 (Kaposi’s Sarcoma-Associated Herpesvirus) Transforming Gene

Abstract: The byline should read as shown above. In addition, permission to cite the unpublished data by Adduci et al. (reference 1) was not obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 0 publications
0
54
0
2
Order By: Relevance
“…We have previously shown that kaposin A, which is one of the proteins expressed during KSHV latency, played crucial roles in KSHV-induced cell proliferation by activating metabotropic glutamate receptor 1 (mGluR1) during KSHV infection (41). Kaposin A has also been shown to mediate oncogenesis in vitro in Rat3 fibroblasts and in nude mice (45,46). Another study by Kliche et al demonstrated the mechanistic role of kaposin A in the oncogenic transformation of NIH 3T3 fibroblasts (47).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that kaposin A, which is one of the proteins expressed during KSHV latency, played crucial roles in KSHV-induced cell proliferation by activating metabotropic glutamate receptor 1 (mGluR1) during KSHV infection (41). Kaposin A has also been shown to mediate oncogenesis in vitro in Rat3 fibroblasts and in nude mice (45,46). Another study by Kliche et al demonstrated the mechanistic role of kaposin A in the oncogenic transformation of NIH 3T3 fibroblasts (47).…”
Section: Discussionmentioning
confidence: 99%
“…Kaposi's sarcoma (KS) is a multicentric neoplasm of vascular origin and very probably of HHV-8 or KSassociated herpes virus etiology (Chang et al, 1994). The kaposin oncogene of the HHV-8 is able to induce tumorigenic transformation and has been found to be expressed in the spindle-shaped cells of this tumor (Ganem, 1997;Muralidhar et al, 1998;Staskus et al, 1997). Kaposi's sarcoma is subdivided into classical KS in older males of mainly Mediterranean or eastern European Jewish backgrounds; endemic KS, found in parts of equatorial Africa; iatrogenic KS, including immunosuppressive drug-associated KS; and AIDS-associated KS.…”
Section: Kaposi's Sarcomamentioning
confidence: 99%
“…Growth stimulation of neoplastic cells may be accomplished in a paracrine manner, as suggested by recent studies of multiple myeloma [40]. Recently, Muralidhar et al [41] demonstrated oncogenicity of a small latency-associated protein named kaposin, which is also produced in HHV-8 cell lines. Alternatively, HHV-8 may sometimes act in conjunction with EBV in causing malignancy.…”
Section: Discussionmentioning
confidence: 99%